PENGARUH TERAPI RELAKSASI BENSON DAN AUTOGENIK TERHADAP PENURUNAN KECEMASAN PASIEN HIPERTENSI - Puling, Dwi M; sutrisno, sutrisno (JURNAL SABHANGA, 2023)
One of the psychological aspects of health problems that arise due to hypertension is anxiety. This problem can have an impact on physical disorders or cause a worse disease prognosis. The purpose of this study was to determine the effect of beson and autogenic relaxation therapy on reducing anxiety in hypertensive patients. The research design used a pre-experimental method with a one group pre-test and post-test design approach. This research was conducted in the working area of the Pukesmas Blowerti Kota Kediri, using a porposive sampling technique to obtain a total of 20 respondents. Data were collected using the HARS questionnaire sheet, and using the Wilxocon analysis test.